2017
DOI: 10.1101/223495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenome-wide association in adipose tissue from the METSIM cohort

Abstract: Most epigenome-wide association studies to date have been conducted in blood. However, metabolic syndrome is mediated by a dysregulation of adiposity and therefore it is critical to study adipose tissue in order to understand the effects of this syndrome on epigenomes. Therefore, to determine if natural variation in DNA methylation was associated with metabolic syndrome traits, we profiled global methylation levels in subcutaneous abdominal adipose tissue. We measured association with 32 clinical traits relate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Some gene loci recently identified to associate with insulin resistance are associated with insulin resistance at a given level of adiposity and modulate insulin sensitivity via adipocyte differentiation 113 , supporting the concept that limited WAT storage capacity rather than overall fat mass is the main contributor to insulin resistance and associated diseases. Epigenetic adipose tissue modifications may further influence these interactions 114 .…”
Section: Adipose Tissue Dysfunctionmentioning
confidence: 99%
“…Some gene loci recently identified to associate with insulin resistance are associated with insulin resistance at a given level of adiposity and modulate insulin sensitivity via adipocyte differentiation 113 , supporting the concept that limited WAT storage capacity rather than overall fat mass is the main contributor to insulin resistance and associated diseases. Epigenetic adipose tissue modifications may further influence these interactions 114 .…”
Section: Adipose Tissue Dysfunctionmentioning
confidence: 99%
“…A recent meta-analysis of EWAS with type 2 diabetes found that the six top CpGs accounted for 11% of the trait variation, which was similar to the variation that could be explained by the common risk factors of BMI, sex, age and smoking [20]. Likewise, in a study for 13 clinical traits in adipose tissue, methylation of the FASN locus alone could account for 16% of the variation in BMI [82]. For comparison, 97 genetic variants discovered in a large GWAS explain only 2.7% of the variance in BMI [83].…”
Section: Dna Methylation and Diseasementioning
confidence: 77%
“…To better explore the relationship between hnRNPs and human lipid traits, we analyzed expression data from the METISM cohort 21 . Interestingly, expression of RALY was positively associated with a number of metabolic, traits including total and LDL serum cholesterol levels though the strength of association was modest ( Fig.…”
Section: Resultsmentioning
confidence: 99%